Systematic sampling of adults as a sensitive means of detecting persistence of lymphatic filariasis following mass drug administration in Sri Lanka. - Ramakrishna U Rao; Sandhya D Samarasekera; Kumara C Nagodavithana; Manjula W Punchihewa; Udaya S B Ranasinghe; Gary J Weil (Public Library of Science (PLoS), 2019)
Background Sri Lanka's Anti-Filariasis Campaign conducted 5 annual rounds of mass drug administration (MDA) with diethylcarbamazine (DEC) plus albendazole to eliminate lymphatic filariasis (LF) in all endemic districts between 2002 and 2006. Post-MDA surveillance has consistently documented Wuchereria bancrofti microfilaremia (Mf) rates below 1% in all sentinel and spot check sites since that time, and all implementation units easily satisfied WHO's target for school-based transmission assessment surveys (school-TAS) in 2013. However, more detailed studies have identified foci of persistent infection in the large coastal evaluation unit (EU) (population about 0.6 million) in Galle district. Therefore, the purpose of this study was to assess the sensitivity and feasibility of community-based TAS in adults (adult-TAS) and to compare results obtained by adult-TAS with prior school-TAS and molecular xenomonitoring (MX, molecular detection of filarial DNA in systematically sampled mosquitoes) results in this known problem area. Methodology and principal findings Two cluster surveys were performed in independent samples of 30 evaluation areas (EAs) in the coastal Galle EU in 2015. Each survey tested approximately 1,800 adults for circulating filarial antigenemia (CFA) with the Alere Filariasis Test Strip. The CFA prevalence for all persons tested (N = 3,612) was 1.8% (CI 1.4-2.2), and this was significantly higher than the CFA rate of 0.4% obtained by school-TAS in 2013. CFA prevalences in the two samples were similar [1.5% (CI 1.0-2.2), and 2.0% (CI 1.4-2.7)]. Antigenemia prevalence in sampled EUs was highly variable (range 0-11%), and it exceeded 5% in 6 EAs. The 30 EAs sampled in one of our adult-TAS surveys had recently been assessed for persistent filariasis by molecular xenomonitoring (MX). CFA prevalence in adults and filarial DNA prevalence in mosquitoes in these EAs were significantly correlated (r = 0.43; P = 0.02). Conclusions Community based adult-TAS provided a reproducible measure of persistent W. bancrofti infection in a large evaluation unit in Sri Lanka that has low-level persistence of LF following multiple rounds of MDA. In addition, adult-TAS and MX results illustrate the focality of persistent LF in this setting. Adult-TAS may be more sensitive than school-TAS for this purpose. Adult-TAS and MX are potential options for post-MDA and post-validation surveillance programs to identify problem areas that require mop-up activities. Adult-TAS should also be useful for remapping areas with uncertain LF endemicity for possible inclusion in national LF elimination programs.